INFLUENCE EXERCISE AEROBICS LOW IMPACT TO COMPLAINT PREMENOPAUSE - Pusparini, Hanna; Jeniawaty, Sherly; Harumi, Ani Media; Nugrahini, Evi Yunita (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
During the premenopausal period there is a sharp decrease in estrogen, an increase in gonadotropins hormones, and hormonal balance disorders which cause several complaints including hot flush, bone and joint disorders, anxiety disorders, insomnia, memory loss, depression, irregular menstruation. This study aims to assess the effect of low impact aerobic exercise on premenopausal complaints. This research is a Pre-Experiment with OneGroupPretest-Posttest Designs. The sample in this study was 39 premenopausal mothers taken using purposive sumpling technique. The independent variable is low impact aerobic exercise, and the dependent variable is premenopausal complaints. Data collection used the MRS questionnaire instrument. Data were analyzed using the Wilcoxon Signed Rank Test with p<0.05. The results of the study showed that there was a decrease in premenopausal complaints after low impact aerobic exercise. From the results of the analysis using the Wilcoxon Signed Rank Test, it was concluded that there was an effect of low impact aerobics exercise on premenopausal complaints, which initially mostly had moderate complaints which changed to mild complaints. After the test was carried out, the results showed that there was an effect of low impact serobic exercise on premenopausal complaints with a p value of 0.000 < α 0.05.